Stability and Economic Performance of the Inflation-Targeting Policy Facing the Crisis - Aguir, Abdelkader (International Journal of Economics and Financial Issues, 2017)
This paper analyzes the inflation targeting policy in emerging economies. More specifically, the development of this work aims to study the conduct, effectiveness and performance of this monetary policy strategy in a context of instability. Taking into account the financial collapse of 2008 and 2009 that has produced the worst global recession since the 1930s. We are developing an econometric approach based on the estimation of the efficiency frontier: variability of inflation - variability of output, which allows us to deduce measures of economic performance and measures of the efficiency of monetary policy. Our results show a significant difference within the macroeconomic performance in a global economic environment characterized by an international financial crisis. We show that these differences are generally due to the choice of this monetary policy strategy. Keywords: inflation targeting, stability, performance, efficiency frontier. JEL Classifications: E52; E63